Usefulness of m-TOR inhibitors in selected dermatological disorders - Osiecka, Karolina; Imko-Walczuk, Beata; Lizakowski, Sławomir; Dębska-Ślizień, Alicja; Rutkowski, Bolesław (Dermatology Review/Przegląd Dermatologiczny, 2011)
Sirolimus, also known as rapamycin, and everolimus are new drugs belonging to the group of pharmaceuticals called m-TOR inhibitors, which have been used in transplantology as immunosuppressive drugs. The m-TOR pathway, also known as m-TOR kinase, plays an important role in cell cycle regulation. m-TOR activation participates in pathogenesis of some diseases, including cancer. A special group of patients, in which rapamycin is recommended in the therapy of carcinoma, comprises patients after organ transplantation, because they carry a higher risk of development of malignant tumours. In dermatology, sirolimus and everolimus have been used in a treatment of tuberous sclerosis complex (TSC) and psoriasis. In therapy of tuberous sclerosis, rapamycin became a fundamental drug, particularly in patients with TSC who need a kidney transplantation. Until now, sirolimus and everolimus have not been tested as monotherapy in psoriasis. However, the m-TOR inhibitors used in association with cyclosporine allowed its dose to be diminished and diminished the nephrotoxicity of this drug. There is still more new information about using rapamycin in the treatment of some other diseases such as skin cancer, kidney cancer, lymphoma or leukaemia.